Tax secrecy provisions: a comparative analysis between Malaysia and other commonwealth countries - Yussof, Salwa Hana; Mohd. Isa, Khadijah; Abdullah, Nurhidayah; Khalid, Maryam (Kluwer Law International, 2025)
Ensuring the confidentiality of taxpayer information is fundamental to fostering trust in tax systems; however, evolving international standards on tax transparency increasingly require tax authorities to share taxpayer information domestically and across borders. This article compares Malaysia’s tax secrecy provisions with those of four Commonwealth jurisdictions: Australia, India, New Zealand, and the United Kingdom. Data were aggregated from legislation, case law, official guidelines, and public domain documents to provide insights into statutory frameworks and practical applications. The study analyses five key dimensions: the scope of confidentiality, statutory exceptions, exchange of information (EOI) across jurisdictions, inter-agency data sharing, and using de-identified data for research purposes. The findings reveal that, while all jurisdictions uphold strict legal protections for taxpayer information, Australia and the United Kingdom adopt approaches that are more transparent and pragmatic providing clear statutory mechanisms for data sharing and public assurance on confidentiality safeguards. In contrast, Malaysia’s broad secrecy provisions and strict interpretation, while relying on ministerial approval, offer limited transparency and risk inconsistent practices. A review of Malaysia’s existing secrecy provisions is recommended along with enhanced public communication to achieve a more balanced approach between confidentiality and transparency in accordance with international best practices.